Tindak Pidana Pencurian dengan Pemberatan yang Dilakukan secara Bersama-Sama; Analisis Putusas Nomor 143/Pid.B/2015/PN.Dmk - Chairunisa Chairunisa; Alfitra Alfitra; Mara Sutan Rambe (JOURNAL of LEGAL RESEARCH, 2021)
The main issue in this study is the judge's inaccuracy in imposing criminal punishment on the perpetrator in a theft case using the weighting of Decision Number 143 / Pid.B / 2015 / PN.Dmk. In Decision Number 143 / Pid.B / 2015 / PN.Dmk, the study aims to identify and analyze the factors behind the occurrence of theft with weighting and consideration of the Judge in imposing crimes against the perpetrators. The findings of this study indicate that the factors underlying the occurrence of criminal acts of theft with weighting in the decision Number 143 / Pid.B / 2015 / PN.Dmk by AD as the perpetrator participated in committing theft with weight, namely economic factors because he was the backbone of the family and had to meet the necessities of life for himself and his family. Then, because all the elements in the primair indictment had been fulfilled, the Judge sentenced the perpetrator to the first charge, namely the perpetrator violating Article 363 Paragraph (1) 3rd, 4th, and 5th of the Criminal Code. The judge has made the right decision, namely trying the perpetrator with a criminal act of theft in burdensome circumstances, but the sentence handed down by the Judge is very minimal and lower than what is demanded by the Public Prosecutor because the perpetrator before committing the crime of theft with weight has just left the Penitentiary (Lapas) with embezzlement cases in Decision Number 133 / Pid.B / 2014 / PN.Pti and have already been convicted. Therefore, the sentence given to the perpetrator is not proportional to what he has done and the judge should also consider the impact and harm caused to the victim as a result of the perpetrator's actions.